Clinical application of the peripheral retinal angiography - J. Turczyńska, Monika; Krajewski, Przemysław; Kęcik, Daria; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
In clinical practice, the posterior pole area is assessed more often than the periphery retina. Fluorescein and indocyanine green angiography (FA and ICGA), optical coherent tomography (OCT), and more recently OCT angiography (OCTA) are standard in the assessment of retinal diseases. OCT and OCTA are currently only used to assess changes in the posterior pole. The authors present their own experience gathered during in the last 15 years of performed angiographic tests of the retina using the following apparatus: FF450 Zeiss, Optos 200Tx and Spectralis HRA + OCT with a 102° wide-angle lens. The authors draws attention to the diagnostic value of wide-field angiography in selected retinal vascular diseases: diabetic retinopathy, retinal vein occlusion, retinal artery occlusion, Susac syndrome, peripheral retinal vascular malformations. They also discuss the use of peripheral angiography in inflammatory diseases of the retina and choroid, white-spot syndromes, nevi and tumors. The authors' own experience indicates the value of performing additional angiograms of the peripheral retina during the assessment of macular diseases, which can highlight changes that often require further diagnostic and therapeutic procedures.